The Colonial Airlines Case: Treaties and Executive Agreements Relating to Aviation - Wenceslas J. Wagner (Washington University Law Quarterly, 1952)
The answer to the question whether the arrangement with Canada was validly entered into by an executive agreement might be based upon either (1) considerations involved in the international relations of the United States generally, or (2) the practice in the field of aviation. The present Article deals only with the second aspect of the problem, the first aspect requiring treatment in a separate work.
Keywords: Air law; Aeronautics